Consumer Behavior Online Shopping in Market Place (Study of Willingness to Buy UR, UIR, UIN and UMRI Riau Student Consumers) - Othman, Lie; Fadli, Mashur; Heriyanto, Meyzi; Jalil, Ashaluddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study was to investigate the factors that influence consumers' willingness to buy on an online platform with research locations on students from the University of Riau, UIR, UIN and UMRI Pekanbaru City and using an explanatory research methodology. This study uses PLS-SEM with Smart-PLS software in analyzing and processing data. Collecting data using a questionnaire using google form with a research sample of 100 consumer students. The results of the study explain that the relationship between perceived reputations (PREP) has no positive and significant effect on the WTB variable with a p-value of 0.093. The t-statistic value is 1.681, the perception of risk (PR) has no positive and significant effect on the WTB variable with a p-value of 0.143. The t-statistic value is 1.469, ease of use (EOU) has no positive and significant effect on the WTB variable with a p-value of 0.198. The t-statistic value is 1.289, the perceived size (PS) has no positive and significant effect on the WTB variable with a p-value of 0.430. The t statistic value is 0.789, the perception of the guarantee system (PSA) has a positive and significant effect on the WTB variable with a p-value of 0.000. The t-statistic value is 7.154, and the Perception of Privacy Information Protection (PPIP) has no positive and significant effect on the WTB variable with a p-value of 0.105. The value of t statistic is 1.623 the perception of the guarantee system (PSA) has a positive and significant effect on the WTB variable with a p-value of 0.000.